(3cJGH GdeYQGLs - (3TgGH GdOjf GdWjHjs ((3YHO GdQRGb Hf MSf HbOhfSs)
(3ChdgG (B:s
(3GdMeO ddg GdPj bQH Edi LfGHg ef CMH hGNJGQg hUjQgbGd Gddg JYGdi (B{(3SHMGf GdPj CSQi HYHOg djdG(B} (3hSFd GdfHj Udi Gddg Ydjg hSde Yf JaSjQ SHMGf abGd gh JfRjg Yf cd ShAs
(3BNQgG (B:s
(3hGNUU CHG HcQ GdMb Hg YeQG (B*** (3cPGc YKeGf Ph GdfhQjf Ke Ydj , hGdBd hGdCUMGH hGdCRhGL CLeYge (B*** (3hGdJGHYjf HEMSGf hcd hJjs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJGQjNs